Diakonia Gereja Pada Remaja Korban Kekerasan Seksual Di Tengah Revolusi Industri 4.0 - Butarbutar, Manuel (Sekolah Tinggi Diakones HKBP, 2024)
The development of technology and the 4.0 Industrial Revolution has brought human to a convenience and pace in doing something. Starting from household chores such as doing the laundry, brewing coffee, cooking rice, and the most prominent one is the information dissemination changed by technology. Nowadays, people do not need to wait long until the letters could be sent because now, only with a thumb, people can send anything to anyone using chat message and online telephone through the gadget. Various conveniences of the internet are wide open to anyone, and it does not recognize age. In the middle of this addicting internet pace, many teenagers are engaged in an association they should not have. Sexual harassment is often perceived by the children who are in a lack of attention from their parents, both verbally and non-verbally. Through Diakonia (Ministry of Love) who empowers teenagers of sexual harassment victims is one of Church’s duties, so they no longer see themselves as a person with no self-esteem and have a willing to continue fixing their life.